Ліси Землі та їх роль у формуванні екологічного світогляду школярів - Коцюбан, Ангеліна Павлівна (My University, 2024)
This master's thesis explores the history, role, and contemporary challenges of Earth's forests. It examines forest evolution from the Paleozoic era to the present, assessing their impact on climate, soil erosion prevention, flood regulation, and pollution reduction. The work analyzes various forest biomes and addresses deforestation and reforestation issues. Special attention is given to the practical implementation of these findings in geography courses for forms 6 to 8, with detailed lesson plans designed to enhance students' environmental education.